Impacts of Brand, Price, and Promotion on Modest Fashion Purchases: Dampak Merek, Harga, dan Promosi terhadap Pembelian Modest Fashion - Elok Zahrotul Lailah; Misti Hariasih (Academia Open, 2024)
This research investigates the influence of Brand Image, Price, and Promotion on Purchase Decisions for Gamis Pelangi Hijab in Driyorejo, employing a descriptive quantitative approach. Utilizing multiple linear regression analysis on data collected from 96 respondents via purposive sampling, the study reveals significant effects: (1) Brand Image positively influences purchasing decisions; (2) Price has a significant impact on purchasing choices; (3) Promotional activities affect purchase decisions. Through regression analysis using SPSS 22, the study elucidates the pivotal role of these factors in consumer behavior, providing insights for marketers aiming to enhance consumer engagement and strategic marketing initiatives in the modest fashion industry. Highlight: Quantitative analysis of purchase decisions for modest fashion. Sample selection based on non-probability purposive sampling technique. Multiple linear regression analysis conducted using SPSS version 22. Keywoard: Gamis Pelangi Hijab, Purchase Decisions, Brand Image, Price, Promotion